PEMODELAN FREKUENSI DAN SIMULASI GETARAN SENAR GITAR BASS LISTRIK DAN GITAR AKUSTIK [FREQUENCY MODELING AND VIBRATION SIMULATION OF ELECTRIC BASS AND ACOUSTIC GUITAR STRINGS] - Gunawan, Caroline; Margaretha, Helena; Cahyadi, Lina; Widjaja, Petrus (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2023)
Mathematical equations can represent numerous real-world scenarios, a process known as mathematical modelling. Within this paper, we undertake modelling two musical instruments, specifically the electric bass guitar and the acoustic guitar. Our approach uses partial differential equations (PDEs) to represent these instruments accurately. By establishing the initial condition, we derive the final solution and simulate the frequency using parameters obtained from this solution alongside a frequency formula. The PDE for the electric bass guitar is of non-homogeneous second order, while the PDE for the acoustic guitar is of homogeneous fourth order. The simulation outcomes demonstrate that a lower vibration frequency for the electric bass guitar corresponds to a decreased string density, given a fixed tension. Similarly, this correlation holds for the acoustic guitar. With fixed string tension and Young's Modulus, a lower string density leads to a higher frequency and reduced inertia. Additionally, we provide graphical representations of the analytical solutions for both PDEs.  Bahasa Indonesia Abstract:Persamaan matematika dapat memodelkan banyak situasi dalam dunia nyata. Proses ini disebut pemodelan matematika. Salah satu contoh yang dapat dimodelkan adalah frekuensi alat musik (gitar bass listrik dan gitar akustik). Kedua alat musik tersebut dimodelkan frekuensinya dengan persamaan diferensial parsial (PDP). Solusi akhir akan diperoleh berdasarkan kondisi awal. Simulasi frekuensi dilakukan berdasarkan parameter yang ditemukan dari solusi akhir dan rumus frekuensi. PDP untuk gitar bass listrik adalah orde dua non-homogen, dan PDP untuk gitar akustik adalah orde empat homogen. Hasil simulasi menunjukkan bahwa untuk gitar bass dengan tegangan tertentu, senar dengan densitas rendah menghasilkan frekuensi getaran yang lebih rendah. Hasil yang konsisten juga ditunjukkan untuk gitar akustik. Pada tegangan senar dan Modulus Young yang diberikan, senar dengan densitas rendah menghasilkan frekuensi yang lebih tinggi dan inersia yang lebih rendah. Beberapa grafik solusi analitik dari kedua PDP tersebut juga ditampilkan dalam artikel ini.